2020
DOI: 10.3390/mi11100910
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Switching in Trilayer Al2O3/HfZrOx/Al2O3 Structure

Abstract: Since ferroelectricity has been observed in simple binary oxide material systems, it has attracted great interest in semiconductor research fields such as advanced logic transistors, non-volatile memories, and neuromorphic devices. The location in which the ferroelectric devices are implemented depends on the specific application, so the process constraints required for device fabrication may be different. In this study, we investigate the ferroelectric characteristics of Zr doped HfO2 layers treated at high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Factors that may explain the improved endurance with the inclusion of Al 2 O 3 into HZO capacitors include (1) the reduction of interface trapped charge and (2) a decrease in oxygen-related defects. Several studies have suggested that the reduction of leakage current density in HfO 2 -based devices with the inclusion of an alumina buffer layer stems from how the Al 2 O 3 layer interacts with oxygen defects in HZO [52,60,61]. It is well-known that TiO x forms at the TiN/HZO interface where oxygen diffuses from the HZO layer to the oxide-electrode and reacts with metallic Ti [29,52].…”
Section: Resultsmentioning
confidence: 99%
“…Factors that may explain the improved endurance with the inclusion of Al 2 O 3 into HZO capacitors include (1) the reduction of interface trapped charge and (2) a decrease in oxygen-related defects. Several studies have suggested that the reduction of leakage current density in HfO 2 -based devices with the inclusion of an alumina buffer layer stems from how the Al 2 O 3 layer interacts with oxygen defects in HZO [52,60,61]. It is well-known that TiO x forms at the TiN/HZO interface where oxygen diffuses from the HZO layer to the oxide-electrode and reacts with metallic Ti [29,52].…”
Section: Resultsmentioning
confidence: 99%
“…4. The achieved Pr of about 10 μC/cm 2 seemed to be observed, but the transition around the Vc occurred slowly [22]. These results were related not only to polarization induced electrons, but also to leakage induced charges, allowing more currents to be included at the large voltage regime.…”
Section: B Trilayer Structure With Alo/hzo/alomentioning
confidence: 92%